EFISIENSI STRUKTUR ALAMI, ANTARA BENTUK DAN SISTEM STRUKTUR - MAER, Bisatya W. (Dimensi: Journal of Architecture and Built Environment, 2012)
This paper discusses building design based on structural efficiency principles of natural objects and creatures. To investigate further about how the efficiency principle is implemented in design, three of Frei Otto’s projects are chosen as case studies. Otto’s project chosen for this study are: the recumbent container which was inspired by a mercury drop; the bell tower of a Protestant Church in Berlin-Schonow which was inspired by Cholla cactus stem; and a branched column inspired by trees. Each of this case is analyzed to find out whether the structural efficiency of these objects are used by Otto from its ‘structural model/ system’ perspective or from the uniqueness of its form. The structural efficiency level of each case is also analyzed. The design of the recumbent container implemented the structural model/ system of the mercury drop’s membrane. The Cholla cactus’s structural model/ system was not implemented as it is but the perimeter structural principal system was developed into different form and structural model/ system. In the last case, the tree’s shape and branches formation were being used to create the branched column’s structure with different structural model/ system. Both three buildings are structurally efficient.